The probability of a sequential Plasmodium vivax infection following asymptomatic Plasmodium falciparum and P. vivax infections in Myanmar, Vietnam, Cambodia, and Laos - von Seidlein, Lorenz (Malar J, 2019)
BACKGROUND: Adding 8-aminoquinoline to the treatment of falciparum, in addition to vivax malaria, in locations where infections with both species are prevalent could prevent vivax reactivation. The potential risk of haemolysis under a universal radical cure policy using 8-aminoquinoline needs to be weighed against the benefit of preventing repeated vivax episodes. Estimating the frequency of sequential Plasmodium vivax infections following either falciparum or vivax malaria episodes is needed for such an assessment. METHODS: Quarterly surveillance data collected during a mass drug administration trial in the Greater Mekong Subregion in 2013–17 was used to estimate the probability of asymptomatic sequential infections by the same and different Plasmodium species. Asymptomatic Plasmodium infections were detected by high-volume ultrasensitive qPCR. Quarterly surveys of asymptomatic Plasmodium prevalence were used to estimate the probability of a P. vivax infection following Plasmodium falciparum and P. vivax infections. RESULTS: 16,959 valid sequential paired test results were available for analysis. Of these, 534 (3%) had an initial P. falciparum monoinfection, 1169 (7%) a P. vivax monoinfection, 217 (1%) had mixed (P. falciparum + P. vivax) infections, and 15,039 (89%) had no Plasmodium detected in the initial survey. Participants who had no evidence of a Plasmodium infection had a 4% probability to be found infected with P. vivax during the subsequent survey. Following an asymptomatic P. falciparum monoinfection participants had a 9% probability of having a subsequent P. vivax infection (RR 2.4; 95% CI 1.8 to 3.2). Following an asymptomatic P. vivax monoinfection, the participants had a 45% probability of having a subsequent P. vivax infection. The radical cure of 12 asymptomatic P. falciparum monoinfections would have prevented one subsequent P. vivax infection, whereas treatment of 2 P. vivax monoinfections may suffice to prevent one P. vivax relapse. CONCLUSION: Universal radical cure could play a role in the elimination of vivax malaria. The decision whether to implement universal radical cure for P. falciparum as well as for P. vivax depends on the prevalence of P. falciparum and P. vivax infections, the prevalence and severity of G6PD deficiency in the population and the feasibility to administer 8-aminoquinoline regimens safely. Trial registration ClinicalTrials.gov Identifier: NCT01872702, first posted June 7th 2013, https://clinicaltrials.gov/ct2/show/NCT01872702. This study was registered with ClinicalTrials.gov under NCT02802813 on 16th June 2016. https://clinicaltrials.gov/ct2/show/NCT02802813